2012
DOI: 10.1177/0021998311430155
|View full text |Cite
|
Sign up to set email alerts
|

Preforms and composites manufactured by novel flax/polypropylene cowrap spinning method

Abstract: In the past decade, natural fiber composites with thermoplastic matrices have been embraced by many composite manufactures for its properties such as lightweight and low cost. Reinforced cowrap spinning yarns and thermoplastics offer a potential for low-cost manufacturing of complex-shaped and good, drapable composite parts, due to reduced impregnation times and resin flow distance during processing. In this article, the cowrap spinning yarns were produced by cowrap spinning method with flax and polypropylene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…By contrast, the basket weaving structure exhibited the lowest tensile elongation (23%), follow by the twill (25%) and the plain structure (27%). This result was consistent with that in a study on flax/polypropylene composites prepared using a cowrap spinning method . The samples with plain and twill weaving structures underwent break‐apart failures (Fig.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…By contrast, the basket weaving structure exhibited the lowest tensile elongation (23%), follow by the twill (25%) and the plain structure (27%). This result was consistent with that in a study on flax/polypropylene composites prepared using a cowrap spinning method . The samples with plain and twill weaving structures underwent break‐apart failures (Fig.…”
Section: Resultssupporting
confidence: 73%
“…Compared with composited with conventional constructions, textile reinforced thermoplastic composites featuring high‐performance light weight structural parts afford advantages for complex light weight applications and multifunctional design. Hybrid yarn manufacturing has been developed recently to process continuous fiber reinforced thermoplastic composites rapidly and cost effectively .…”
Section: Introductionmentioning
confidence: 99%
“…For 50:50 weight ratio, B Flax + B Matrix fibres = 1, so that the total 3% of filaments in the yarns were used as the core blends of yarn (flax/matrix, 50/47% by wt) were fixed. It was also found by researchers that the filament turns/m influences the total matrix weight fraction in the yarn structure [18]. In this work, it was found that filament wrapping angle has influenced the yarn strength, where the average breaking loads of 19.5N with breaking extension of 5.5% were found for 44.6˚ wrapping angle.…”
Section: Fibre-matrix Blendssupporting
confidence: 52%
“…This mechanism is also established by many modern techniques such as soft X-ray Therefore, there is a demand to adopt a new cost-saving technology for using of MA grafted PP fibres with untreated natural fibres to obtained better me-Journal of Textile Science and Technology chanical properties of composites. In previous work, flax/PP hybrid thermoplastic yarns and fabrics were treated by MA coupling agent [18] before hot-pressing but those were preliminary investigations and not economically feasible as they are wet processes, which require additional cost for drying after the treatment of the fabrics.…”
Section: Introductionmentioning
confidence: 99%
“…Many currently manufactured textile products already contain recycled PET (rPET) fibers, and their use for the development of novel srPC composites fits the described 'upcycling' strategy relatively well. Hybrid or commingled yarns can also be used as suitable preforms of srPET composites since they can be processed on the existing industrial lines and, therefore, easily converted to different textile architectures [10,11]. Co-wrap spinning commingled methods were also utilized to successfully prepare self-reinforced recycled PET (srrPET) composites in the authors' laboratory from the rPET/copolymerized PET (mPET) commingled yarns [12][13][14][15], and their open-hole tensile properties [14], fracture behavior, and damage development [13] have been recently investigated.…”
Section: Introductionmentioning
confidence: 99%